Soil quality and spatial variability assessment of tropical peat (histosol) soil cultivated with cassava (Manihot esculenta Crantz) in Sepang, Selangor, Malaysia - Kabir, Adebayo Kayode (2022)
Tropical peats are generally acidic (pH 3.0-4.5) and deficient in nutrients such as Ca, Mg, K, P, Mn, Fe, Zn and Cu. Therefore, liming materials (calcium carbonate (CaCO3), magnesium carbonate (MgCO3), dolomite (CaMg (CO3)), magnesium oxides (MgO)) is commonly practiced besides the use of chemical fertilizers and other cocktail of agrochemicals to improve selected soil characteristics and to produce satisfactory yield. Furthermore, no standardized method is available on soil quality assessment especially peat. Noteworthy that, various approach and indices have been applied by researchers globally. Therefore, the objective of this present study is to classify and characterize the tropical peat (soil) in the study area, to determine, evaluate and assess the tropical peat (soil) quality (fertility status) using selected quality indices (Soil Fertility Index (SFI), Soil Quality Index (SQI), and Soil Microbial Index (SMI)) and to further produce the peat soil spatial variability by semivariogram of selected crop-nutrients. This study was conducted at Taman Kekal Pengeluaran Makanan (TKPM) Ulu Chucoh, located in Sepang district in the southern part of the state of Selangor, Malaysia (latitude 02°451 N and longitude 101°401 E). Soil in the study area were mainly peat (up to 80 cm depth) and underlain by mineral soils. A total of 150 soil samples were collected at five (5) different depths (0-20 cm, 20-40 cm, 40- 60 cm, 60-80 cm and 80-100 cm) at each determined grid (total 30 grids) using a hand auger. The soil samples were subjected to morphological, physical and chemical analysis (properties), biological (microbial) and selected heavy metals analyses, based on standard methods well-stated in the literature. Descriptive statistics were analyzed using Analysis of Variance (ANOVA) and the Least Significant Difference (LSD) was used for mean separation at p≤0.05 using SAS version 9.4 software. The geostatistical method was used to generate spatial map for SFI, SQI and major soil nutrients of the study site for all the depths using ArcGIS 10.7.1 software. The soil chemical properties were significantly difference with varying depth at p≤0.05 level of LSD test. Results showed that the peat (soil) in the study area ranged from very strongly acidic to a strong acidic (pH 3.30 to 4.64). Soil organic carbon (SOC) showed a decreasing value with increasing depth (17.64 to 9.31